Measurement Efficiency of a Teacher Rating Scale to Screen for Students at Risk for Social, Emotional, and Behavioral Problems - Gino Casale; Moritz Herzog; Robert J. Volpe (Journal of Intelligence, 2023)
Teacher rating scales are broadly used for psycho-educational assessment in schools. In particular, they play an important role in screening students for social, emotional, and behavioral problems. In order to optimize the efficiency of these measures, it is important to minimize the number of items comprising them while maintaining sound psychometric characteristics. This study examines the measurement efficiency of a teacher rating scale for student social, emotional, and behavioral risk. The goal was to shorten an existing behavior screening tool. A total of 139 classroom teachers and 2566 students from Grades 1–6 (Mage = 8.96 years, SD = 1.61) participated in the study. In sum, 35 items assessing internalizing and externalizing behavior problems were analyzed applying the item response theory (generalized partial credit model). The results show that social, emotional, and behavioral risks can be captured with a total of 12 items. This reduction of almost 66% of the initial item pool would take teachers about 90 s to fill out for one student. Thus, the rating scale can be used by teachers in an efficient yet psychometrically sound manner.